Depressão e priming de palavras positivas, neutras e negativas - Poinhos, Rui (2015)
The objective of this study was to investigate the association between the level of depression in a nonclinical sample and the performance on implicit memory (priming) tasks. One-hundred and twenty university students aged between 18 and 27 years were randomly divided into two groups (conditions) based on different learning tasks but including the same word-stem completion task. The independent variable was the level of depression. The independent variable was the level of depression (Inventory of Clinical Assessment of Depression). The stimuli used were positive, neutral, and negative words. The results show a relationship between higher cognitive symptoms of depression and a reduced performance on word completion, and they suggest preferential processing of emotional congruent stimuli with the level of depression and the secondary activation of emotional stimuli by stimuli of opposite valence. Keywords: Self congruence; Depression; Humor; Cognitive process.